Analisa dan Perancangan Aplikasi Sistem Penyewaan Kendaraan berbasis Java - Septi Nur Ilmi Putri; Mohammad Zaeni; Desi Jasmiati; Endar Nirmala; Irpan Kusyadi (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Rental is a service provider that provides vehicle rental services. Currently, there are still many rental businesses that use manual systems for data processing which results in less efficient and slow work. Lack of information also makes it difficult for prospective tenants to find out the vehicle you want to rent. Making this application design aims to help facilitate ordering and information. This vehicle rental application will be designed using the Unified Modeling Language (UML) method, which visualizes the modeling using Use Case Diagrams and Activity Diagrams. Then the programming language that will be planned is JAVA language, with the MYSQL database as data storage. Meanwhile, the application development uses the Netbeans IDE 8.2. This system will provide results in the form of rental information and ordering transactions to facilitate vehicle rental activities.